Mirror neuron brain regions contribute to identifying actions, but not intentions - Thompson, EL; Bird, G; Catmur, C (Wiley, 2022)
Previous studies have struggled to determine the relationship between mirror neuron brain regions and two distinct “action understanding” processes: identifying actions and identifying the intentions underlying those actions. This may be because the identification of intentions from others' actions requires an initial action identification process. Disruptive transcranial magnetic stimulation was administered to left inferior frontal gyrus (lIFG) during a novel cognitive task to determine which of these “action understanding” processes is subserved by mirror neuron brain regions. Participants identified either the actions performed by observed hand actions or the intentions underlying those actions. The extent to which intention identification was disrupted by lIFG (vs. control site) stimulation was dependent on the level of disruption to action identification. We subsequently performed functional magnetic resonance imaging during the same task. During action identification, responses were widespread within mirror neuron areas including lIFG and inferior parietal lobule. However, no independent responses were found in mirror neuron brain regions during intention identification. Instead, responses occurred in brain regions associated with two distinct mentalizing localizer tasks. This supports an account in which mirror neuron brain regions are involved in an initial action identification process, but the subsequent identification of intentions requires additional processing in mentalizing brain regions.